Total colectomy in a gangrenous large bowel due to a rare double closed loop obstruction. (2015) - Sali, Priyanka Akhilesh; Pilania, Vineet; Sutar, Sudhir; Krishna, Kumar; Ghetla, Smriti; Shetty, Tilakdas
Highlights: Dual closed loop obstruction: one due to the sigmoid volvulus and the other due to a competent ileocaecal valve. Gangrene of the entire large bowel from the ileo caecal junction till the distal end of sigmoid. Total colectomy done for such necrotizing colitis. Rapidity of ischaemic changes in a closed loop obstruction. Abstract: Introduction: Closed loop obstruction is commonly encountered in sigmoid volvulus. When such obstruction becomes fulminant, it is called acute necrotizing colitis. Gangrene of the entire large bowel from the caecum till the distal end of the sigmoid is a rare entity. Presentation of the case: We present here one such case of necrotizing colitis in a 27 years old gentleman who presented with large bowel obstruction and septic shock. Computed tomography (CT) revealed sigmoid volvulus with ischaemic changes. The rest of the colon was dilated. On laparotomy, a gangrenous sigmoid due to the volvulus was found along with complete gangrene of the proximal bowel from the ileocaecal junction till the volvulus. This was probably due to a double closed loop obstruction, one at the sigmoid volvulus and the second being between a probable competent ileocaecal valve and the proximal end of the volvulus. A total colectomy with an end ileostomy was performed. Discussion: Necrotising colitis involving the entire colon is seldom seen. Large bowel obstruction is a known surgical emergency due to a probable closed loop obstruction due to a competent ileocaecal valve. Conclusion: To our knowledge, such gangrene of the entire large bowel due to a sigmoid volvulus and a competent ileocaecal valve has not been reported in literature so far. We also highlight here, the rapid ischaemic changes that follow a closed loop obstruction. In our case the CT has shown ischaemic changes only in the sigmoid. Hence, timely diagnosis and intervention is imperative.